On the importance of geological data for three-dimensional steady-state hydraulic tomography analysis at a highly heterogeneous aquifer-aquitard system - Zhao, Zhanfeng; Illman, Walter A. (Journal of hydrology (Amsterdam), 2017)
•We investigate the value of geological data on HT at a highly heterogeneous site.•HT analyses are conducted with different model conceptualizations.•The geostatistical approach performs the best in model calibration and validation.•Integrating reliable geological data improves the geostatistical inversion results. Hydraulic tomography (HT) has been shown to map subsurface heterogeneity accurately through the joint interpretation of multiple pumping tests. Previous research has shown that smooth hydraulic conductivity (K) estimates are obtained beyond where pumping/observation data are available using the geostatistical inversion approach, when the inversion begins with a homogeneous K and when data densities are not high. However, geological data are typically available through outcrops and borehole logs to provide geological variability. Therefore, we investigate the usefulness of geological data for HT analysis at a highly heterogeneous field site by: (1) comparing calibrated geological models of two different resolutions to two homogeneous and four highly parameterized geostatistical inverse models, in terms of both model calibration and validation performances as well as correspondence of estimated K values with permeameter-estimated K profiles along boreholes; and (2) using geological models as prior information for the geostatistical inversion approach. Results reveal that the simultaneous calibration of geological models to seven pumping test data yields K values that correctly reflect the general patterns of vertical distributions of permeameter-estimated K. We also find that the geostatistical inversion approach using a geological model as prior information performs better for both model calibration and validation than using a homogenous K as a prior, and more importantly, improves the correspondence of K estimates to permeameter test results along wells, as well as in preserving geological features where drawdown measurements are lacking. Overall, our results suggest the joint use of both geological and pumping test data for HT analysis when accurate geological data are available.